1986
DOI: 10.1149/1.2108392
|View full text |Cite
|
Sign up to set email alerts
|

Glow Discharge Electrolysis of Aqueous Sulfuric Acid Solution in Various Atmosphere

Abstract: The anode glow discharge electrolysis was carried out in aqueous sulfuric acid solution, and the yields of oxidation products, H202, H2SO.~, and H2S208, were examined in various atmospheric gases, H2, He, N2, and Ar. When the vapor pressure of water was suppressed by means of intermittent electrolysis, the yields of the peroxides were found to depend clearly on the atmospheric gases. The plasma diagnostics, emission spectra, double-probe method, etc., revealed that the plasma state in the gas phase depended on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…The direct contact of an aqueous electrolyte and a plasma anode as a unique electrochemical technique, the so called glow discharge electrolysis (GDE), has been used solely to produce peroxide compounds in the electrolyte [1,2,3,4,5,6]. The product yields and the influence of the glow discharge plasma on the oxidation processes taking place in the solution were thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct contact of an aqueous electrolyte and a plasma anode as a unique electrochemical technique, the so called glow discharge electrolysis (GDE), has been used solely to produce peroxide compounds in the electrolyte [1,2,3,4,5,6]. The product yields and the influence of the glow discharge plasma on the oxidation processes taking place in the solution were thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Points for 0.5 and 1 mol/L activity are calculated from U cf values reported in[1] and[4], respectively…”
mentioning
confidence: 99%
“…The interaction of discharge plasmas with liquids [1][2][3][4][5] is one of the active topics in the realm of recent plasma science and science technology. It has pioneered new channels relating to nano material creation based on their distinct properties such as ultra-high density, high reactivity, high process rate, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It was conventionally performed in a gas/liquid dual-phase system, in which two asymmetric electrodes were placed close to or in the electrolyte, and the plasma was ignited on the surface of the working electrode under a high cell potential. Many works have already been conducted in order to obtain a comprehensive understanding of the GDE [2][3][4], and it is found that the main influencing factors in the formation of the plasma are applied potential, geometries of electrodes, temperature of the electrolyte, properties of the electrolyte, and its flow dynamics [5]. It is well known that an obvious feature of the GDE process is the non-Faraday behavior [2,6], that is, the chemical yield around the discharge electrode is much higher than those calculated from the Faraday law.…”
Section: Introductionmentioning
confidence: 99%